Comparison of Three Complementary Analytical Techniques for the Evaluation of the Biosimilar Comparability of a Monoclonal Antibody and an Fc-Fusion Protein - Demelenne, Alice; Ben Yahia, Arij; Lempereur, Delphine; Crommen, Jacques; Servais, Anne-Catherine; Fradi, Ines; Fillet, Marianne (Frontiers in Chemistry, 2021)
The number of monoclonal antibodies and derivatives such as Fc-fusion proteins available on the market is rapidly increasing. With the expiration of their patents, biosimilars are emerging. Biosimilars represent medicines that are highly similar but not identical to the reference products. To assess the comparability between those products, dedicated analytical methods are required. In this work, a monoclonal antibody, adalimumab, and a Fc-fusion protein, etanercept, were studied and compared to one of their biosimilars. Samples submitted to stress conditions (agitation and high temperature) were used for method development. The developed methods were also applied to samples reduced by beta-mercaptoethanol (BME) to evaluate their capability to distinguish the expected species. Capillary gel electrophoresis (CGE), reversed-phase liquid chromatography (RPLC) and size-exclusion chromatography (SEC) methods coupled with UV detection were used to analyze the biopharmaceuticals. Their complementarity was investigated. For further molecular weight determination, SEC- multi-angle light scattering (MALS) and RPLC-quadrupole time-of-flight (QTOF) were occasionally used. For adalimumab, a larger amount of fragments and aggregates was observed in the biosimilar compared to the reference product. For etanercept, more related species were found in the reference product. Those three separation techniques showed good complementarity. Indeed, RPLC enabled the separation of hydrophilic and hydrophobic degradation products. CGE provided good selectivity for several adalimumab fragments and SEC was useful for the analysis of aggregates and certain fragments that cannot be separated by the other approaches. Moreover, those formulations were submitted to mild stress conditions (30°C, 300 rpm for 4 hours) that mimic shipping conditions. No additional peak was found under these conditions for the two studied biopharmaceuticals.